Exploring wellbeing in the context of family tourism - Kariyawasam, C.D.P. (University of Colombo, Sri Lanka., 2019)
In their study on factors affecting subjective well-being Lamu and Olsen (2016) highlight the significance of social relationships as the most important determinant of subjective well-being, surpassing the importance of factors such as health related quality of life and household income. In this context, this paper seeks to explore the notion of wellbeing in relation to family tourism, in an attempt to gain deeper understanding of how social relationships influence one's sense of well-being. This paper attempts to resist the individualised idea of health and wellbeing, arguing that these notions need to be understood as social phenomena. Material for this study will be drawn from data collected at two field sites, Galle Fort in Galle and Galle Face in Colombo, both popular leisure destinations by the beach, where people come to play informal games, have picnics, fly kites, jog, exercise or merely gaze at the sea and take in the air. Paying close attention to the material collected from local families at these locations and from interviews conducted with individuals and families, the paper attempts to lay out experiences of families at leisure and seeks to ascertain their meanings and understandings of wellbeing.
Keywords: family, social relationships, tourism, travel, wellbeing